2016
DOI: 10.1089/ten.teb.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

EmergingIn VitroLiver Technologies for Drug Metabolism and Inter-Organ Interactions

Abstract: In vitro liver models provide essential information for evaluating drug metabolism, metabolite formation, and hepatotoxicity. Interfacing liver models with other organ models could provide insights into the desirable as well as unintended systemic side effects of therapeutic agents and their metabolites. Such information is invaluable for drug screening processes particularly in the context of secondary organ toxicity. While interfacing of liver models with other organ models has been achieved, platforms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 70 publications
(82 reference statements)
0
42
0
Order By: Relevance
“…PHHs are essential tools in the assessment of drug transporters, a feature of drug metabolism that subcellular fraction models do not address [27, 28]. Unfortunately, PHHs lose proliferative ability in isolation and have significant variability in enzyme expression, causing cell source limitations [29]. Nevertheless, there have been a number of promising efforts to induce PPH culture expansion [30, 31].…”
Section: Biological Assessment Of Drug Metabolism In Preclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…PHHs are essential tools in the assessment of drug transporters, a feature of drug metabolism that subcellular fraction models do not address [27, 28]. Unfortunately, PHHs lose proliferative ability in isolation and have significant variability in enzyme expression, causing cell source limitations [29]. Nevertheless, there have been a number of promising efforts to induce PPH culture expansion [30, 31].…”
Section: Biological Assessment Of Drug Metabolism In Preclinicalmentioning
confidence: 99%
“…This particular dimension of drug metabolism is logistically difficult and uneconomical in in vivo approaches. An area where in vivo models have the advantage is in multi-organ and inter-organ interactions, but innovative cell-culture systems for liver-based multi-organ models are beginning to have an impact, as reviewed by Bale et al [29]. …”
Section: Biological Assessment Of Drug Metabolism In Preclinicalmentioning
confidence: 99%
“…Godoy et al (2013) reviewed in detail besides other aspects the possibilities, limitations, and pitfalls of the various liver cell models. Recently, Bale et al (2016) reviewed current liver-based multi-organ cell culture platforms primarily from a drug and metabolite perspective and highlighted the importance of cell-to-media ratio in interfacing liver models with other organ models. Further discussion on the suitability of various liver models for DoA metabolism studies can be found in the recent review article of Meyer (2016).…”
Section: Hrms For Elucidation Of the Metabolite Structures And Formatmentioning
confidence: 99%
“…With hepatotoxicity accounting for >35% failures in drug development processes, there is a substantial need for comprehensive, predictive models capturing hepatic function, feedback and responses (Mehta, Editor, & Pinsky, ; Olson et al, ; Schuster, Laggner, & Langer, ). To obtain human鈥恟elevant information, several in vitro cell culture systems (comprising cells and matrix materials from both animal and human sources) have been developed (Bale & Borenstein, ; Bale et al, ; Bale, Moore, Yarmush, & Jindal, ; Bjornsson et al, ; Ewart et al, ; Godoy et al, ; Greaves et al, ; Materne, Tonevitsky, & Marx, ; Soldatow, Lecluyse, Griffith, & Rusyn, ). The primary focus of in vitro hepatic cell culture systems has been primary human hepatocyte (PHH) stabilization and long鈥恡erm culture, achieved using collagen sandwich (Dunn, Tompkins, & Yarmush, ), spheroid (Messner, Agarkova, Moritz, & Kelm, ), 3D printing (Nguyen et al, ), and micropatterning (Khetani & Bhatia, ) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The primary focus of in vitro hepatic cell culture systems has been primary human hepatocyte (PHH) stabilization and long鈥恡erm culture, achieved using collagen sandwich (Dunn, Tompkins, & Yarmush, ), spheroid (Messner, Agarkova, Moritz, & Kelm, ), 3D printing (Nguyen et al, ), and micropatterning (Khetani & Bhatia, ) techniques. In addition to static systems, high鈥恡hroughput in vitro models and advanced dynamic microfluidic systems are emerging as tools to predict ADMET attributes, and disease modeling in particular (Bale et al, ; Bale, Moore, et al, ; Bhatia & Ingber, ; Ewart et al, ; Hughes, Kostrzewski, & Sceats, ; Materne et al, ). Further, these organ鈥恛n鈥恈hip systems have the potential to elucidate molecular and cellular phenotypes of rare diseases, and aid in drug development (Low & Tagle, ; Low & Tagle, ).…”
Section: Introductionmentioning
confidence: 99%